Factors Associated with Self-Esteem among Undergraduate Students of Pokhara Metropolitan, Nepal: A Cross-sectional Study - Paudel, Shishir (Europasian Journal of Medical Sciences, 2020)
Background: Self-esteem is an overall subjective evaluation of one’s worth or value which encompasses the positive or negative orientation or beliefs towards oneself. Self-esteem has established itself as an important psychological factor contributing to health and quality of life. Thus, this study aimed at understanding the factors influencing the level of self-esteem among the undergraduate students and its correlation with depression, anxiety and stress symptoms experienced by the students. Methods: A cross-sectional study was conducted among 618 randomly sampled undergraduates from different academic institutions of Pokhara Metropolitan. We used Rosenberg self-esteem scale to assess the level of self-esteem and DASS-21 to assess the level of depression, anxiety, and stress. The collected data was analyzed using SPSS statistical software. The chi-squire test, binary logistic regression and Pearson correlation analysis were performed to establish the relationship between variables at the level of significance, p<0.05. Results: More than three-forth (75.7%) of the students were found to have a normal level of self-esteem while around one-fifth (21.4%) of the students had low self-esteem. There was no statistical relationship established between students’ academic discipline and their self-esteem. However, students’ academic performance, family history of any psychological distress and their perceived level of social support were the major influencing factors associated with their self-esteem at p<0.001. Based on Pearson correlation analysis, self-esteem was negatively correlated with depression, anxiety and stress at p<0.01. Conclusion: The students’ level of perceived social support, family history of psychological disorder and academic performance are statistically associated with student’s level of self-esteem. Furthermore, there existed a negative correlation between self-esteem and depression, anxiety and stress experienced by the students. Thus, strategies aimed to increase students’ level of perceived social support and self-esteem can reduce their risks of acquiring any mental health problems in near future.